SOCIOLINGUISTIC INTERACTION OF SOCIETY IN BUSUNGBIU DISTRICT BULELENG REGENCY - Elly, Kadek; Rasna, I Wayan; Suandi, I Nengah (Jurnal Penelitian dan Pengembangan Sains dan Humaniora, 2019)
The purpose of this research to (1) describe the language variations in sociolinguistic interaction of society in Busungbiu district Buleleng Regency, (2) to describe the language choice in sociolinguistic interaction of society in Busungbiu district Buleleng Regency, and (3) to describe the factors that affect language variations and language choices in sociolinguistic interaction of society  in Busungbiu district Buleleng Regency. Data were collected using observation and interview. The data are analyzed through reduction, presentation and data collection. The location of this research is 4 of 15 villages in Busungbiu sub-district that is Sepang Village, Pelapuan, Kekeran, and Busungbiu. The result of this research shows that (1) There are language variations in terms of speakers of dialect and sociolek and language variations in terms of formality. (2) There is a code switching of the Bali language code into the Indonesia language, code switching the Indonesia language code into Bali language, code switching the Java language code into the Indonesia language. The code mixing into and code mixing exit. (3) Factors that influence is the language variation that is area of the speaker's and social origin. Factors that influence is the language choice that is changing speech situations, the presence of a third person, awakens a sense of humor, to a mere prestige, using more popular terms. Thus it can be concluded that the Bali language experiencing critical condition and bali language start to weaken. This can be proved by the existence of citizens who notabene native Bali language speakers can code switch and code mixed, so the use of Bali language began to shift little by little. Based on this, the need for guidance, training and coaching, especially the Bali language in Busungbiu district.